Wilson’s disease presenting as resistant rickets without Fanconi syndrome - Patel, Bhavin; Sardana, Vijay (Indian Journal of Case Reports, 2020)
Wilson’s disease is a disorder of copper metabolism which usually presents with neurological or hepatic manifestation. Wilson’s disease presenting as a musculoskeletal disorder is rare. We are reporting the case of a 12-year-old male boy presented with resistant rickets followed by dysarthria. The patient was diagnosed as having Wilson’s disease based on Kayser–Fleischer ring on examination, high 24 h urinary copper level, and magnetic resonance imaging brain changes. This case highlights that in the case of resistant rickets, a high index of suspicion for Wilson’s disease should be kept. Early recognition of this entity results in timely treatment and prevention of significant disability.